Sinusoidal alternating current heating strategy and optimization of lithium-ion batteries with a thermo-electric coupled model. (1st November 2019) - Li, Junqiu; Sun, Danni; Chai, Zhixiong; Jiang, Haifu; Sun, Chao
Abstract: In order to solve the application bottleneck of electric vehicles in alpine-cold regions, sinusoidal alternating current heating becomes a competitive method. A novel thermo-electric coupled model for lithium-ion power batteries at low temperatures is proposed in this paper. The model combines the thermal model with the electrochemical impedance model. Model parameters are identified by genetic algorithm through programming in MATLAB. Plenty of experiments have validated the model and explored the influence factors of the heat generation effect. It is found that as the battery temperature increases, the optimal current amplitude increases gradually, whereas the optimal current frequency decreases. Therefore, an original temperature dependent control approach of sinusoidal alternating current heating is proposed and the strategy is optimized by sequential quadratic programming algorithm, considering safe operating voltage constraints. The optimal frequency range is distributed in the high frequency region, which makes the allowable safe current larger and thus gives a larger heat generation rate, and lithium ion deposition does not occur. Finally, the optimized heating strategy is verified by experiments. Results show that the battery module can achieve a temperature rise from −20 °C to 0 °C in 520 s, with an average temperature-rise 2.31 °C/min. Highlights: A novel thermo-electric coupled model for Li-ion battery at low temperatures. A temperature dependent strategy and optimization of sinusoidal AC heating. Experiments were conducted to verify the model and the proposed strategy.